2013
DOI: 10.1016/j.febslet.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid differentiation is augmented in Reelin‐deficient K562 cells and homozygous reeler mice

Abstract: a b s t r a c tReelin is an extracellular glycoprotein that is highly conserved in mammals. In addition to its expression in the nervous system, Reelin is present in erythroid cells but its function there is unknown. We report in this study that Reelin is up-regulated during erythroid differentiation of human erythroleukemic K562 cells and is expressed in the erythroid progenitors of murine bone marrow. Reelin deficiency promotes erythroid differentiation of K562 cells and augments erythroid production in muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Initially, liver cells secreting reelin into the circulation were proposed as the major source of reelin found in the blood plasma (Smalheiser et al, ). Further studies defined RELN as an erythroid‐enriched gene, and confirmed that blood cells, such as erythrocytes and platelets, also produce reelin protein (Jacquel et al, ; Redmond et al, ; Tseng et al, ; Redmond et al, ; Chu et al, ).…”
Section: Reelin Signaling Activity In Adult Non‐neuronal Tissuesmentioning
confidence: 88%
See 3 more Smart Citations
“…Initially, liver cells secreting reelin into the circulation were proposed as the major source of reelin found in the blood plasma (Smalheiser et al, ). Further studies defined RELN as an erythroid‐enriched gene, and confirmed that blood cells, such as erythrocytes and platelets, also produce reelin protein (Jacquel et al, ; Redmond et al, ; Tseng et al, ; Redmond et al, ; Chu et al, ).…”
Section: Reelin Signaling Activity In Adult Non‐neuronal Tissuesmentioning
confidence: 88%
“…In heterozygous reeler +/‐ mice, levels of circulating reelin are half of those found in wild‐type littermates, and the protein is absent from the plasma of reeler ‐/‐ mice (Smalheiser et al, ). reeler ‐/‐ mice also have higher red blood cell (RBC) counts compared with wild‐type controls, without changes in spleen size (Chu et al, ). Higher RBC numbers are also observed in the reeler ‐/‐ bone marrow, concomitant with attenuation of phosphorylated Akt (Chu et al, ).…”
Section: Reelin Signaling Activity In Adult Non‐neuronal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reelin mRNA is found in the small intestine, where the epithelium has a high turnover rate and is subject to rapid renewal [218]; reelin is also involved in the processes of osteogenesis and dentinogenesis [219,220]. Moreover, reelin is expressed in hepatic stellate cells of the liver, an organ that is self-regenerative [221,222], along with the blood [221,223], mammary gland [224], and the bovine and chicken endometrium and ovarian follicle [225,226]. Though its exact mechanisms of action in these widespread systems are unclear, the pervasive nature of reelin, despite its large size and the energy required to secrete it, points to a broad but significant role in the development of a diverse set of organs and tissues.…”
Section: Identifying Features and Functional Roles Of Major Neurocmentioning
confidence: 99%